Quality reliability analysis of flash welding joint of cold-rolled 50JW800 silicon steel strip. (August 2022) - Xu, Youwei; Yang, Binhui; Shi, Yu; Feng, Xudong; Li, Jipeng; Feng, Changgen; Volodymyr, Korzhyk
Highlights: Quality reliability of flash butt-welded 50JW800 Si steel strip joints was assessed. Assessed metallographically and by cupping, tensile, and eddy current testing. Eddy current testing adequately assessed the weld joint microstructural traits. Insufficient recrystallization at weld joint causes breaks during cold rolling. Eddy current tests can assess the reliability of 50JW800 Si steel strip FBW joints. Abstract: In this study, the quality reliability of the flash butt welding (FBW) joint of a 50JW800 silicon steel strip is analyzed through metallographic observation, cupping tests, and tensile tests. It is found that the recrystallization in some areas of the joint is insufficient, as is the mechanically forced connection, owing to the plastic deformation and uneven heat distribution of the joint during the process of FBW. Insufficient recrystallization is the root cause of strip breakage during cold rolling. The quality reliability of the 50JW800 silicon steel strip FBW joint is also analyzed using eddy current nondestructive testing technology. It is found that the eddy current testing signal has a good response to different structural characteristics of the joint. Therefore, eddy current test technology can be used to ensure the quality reliability of silicon steel strip FBW joints in actual production.